Volunteer Work for Developing Skills in Prospective Specialists in Physical Culture and Sports - Maliarenko, Iryna; Kedrovskyi, Borys; Romaskevych, Yurii; Koltsova, Olha; Маляренко, Ірина; Кедровський, Борис; Ромаскевич, Юрій; Кольцова., Ольга (Східноєвропейський національний університет ім.Лесі Українки, 2017)
rofessional training assumes the formation of the young generation of spiritual values and ideals, behavioral stereotypes and concrete actions. The purpose of the research was to analyze the directions of using volunteer activity in the formation of professional and social competencies of students of the Faculty of Physical Education and Sports.The realities of the training of specialists allowed us to single out professional and social competencies as a separate species. The graduate should have an understanding and perception of ethical norms of behavior, understand the need to observe the norms of a healthy lifestyle, be creative, sociable, tolerant. In his professional work should provide for the prospects of working with the formation of a system of goals, to design the content of educational and upbringing activities with self–monitoring and self–evaluation of the work performed.It is determined that the pedagogical functions of volunteer activity are the orientation of the individual in social relations; The creation of an educational space; Ensuring the possibility of acquiring the experience of social and communicative interaction. The experience of using volunteer activity testifies to the need to ensure the unity of theoretical knowledge and practical activity, which is represented by the «model of formation» using different forms of organi-zation in the following areas: educational, sports and social component within the framework of the students' practical training of the faculty of physical education and sport.To assess the effectiveness of experimental work on the impact of volunteer work on the formation of professional and social competence, we used quantitative and qualitative assessments, which express the changes in the characte-ristics of individual students. In terms of readiness of the future teacher to education of students was recorded positive trend: students with low level of readiness was 36,4 % less; middle and high readiness –more by 26,4 and 11,1 % respectively, confirming the effectiveness of educational practice using components of volunteering and its impact on the formation of professional and social competencies.Analyzing the experience of using volunteering at the Faculty of Physical Education and SportsKherson state university note that it promotes the professional experience of moral consciousness; encourages the development of motivational sphere student, his personal qualities, aspiration to self-development, to expand professional competence. Професійна підготовка передбачає формування в молодого покоління духовних цінностей та ідеалів, поведінкових стереотипів і конкретних вчинків. Мета дослідження –проаналізувати напрями використання волонтерської діяльності у формуванні професійно-соціальних компетентностей студентів факультету фізичного виховання та спорту.Реалії підготовки фахівців дали нам підставу виокремити професійно-соціальні компетентності як окремий вид. Випускник повинен володіти розумінням та сприйняттям етичних норм поведінки, усвідомлювати необхідність дотримання норм здорового способу життя, бути креативним, комунікабельним, толерантним. У своїй професійній діяльності потрібно передбачати перспективи роботи з формуванням системи цілей, конструювати зміст освітньо-виховної діяльності із самоконтролем та самооцінкою виконаної роботи.Визначено, що педагогічними функціями волонтерської діяльності є орієнтація особистості в соціальних відносинах, створення виховного простору, забезпеченняможливості набуття досвіду соціально-комунікативної взаємодії. Досвід використання волонтерської діяльності свідчить про необхідність забезпечення єдності теоретичних знань і практичної діяльності, що представлена «моделлю формування» з використанням різних форм організації за такими напрямами, як освітня, спортивна та соціальна складові частини в межах навчальних практик.Для оцінки результативності експериментальної роботи щодо впливу волонтерської роботи на формування професійно-соціальної компетентності ми користувалися кількісними і якісними оцінками, які виражають зміни в характеристиках окремих студентів. За критерієм готовності майбутнього педагога до виховання учнів зафіксовано позитивну динаміку: студентів із низьким рівнем готовності стало на 36,4 % менше; із середнім та високим рівнями готовності –більше на 26,4 і 11,1 % відповідно, що підтвердило ефективність проведення навчальної практики із застосуванням складників волонтерської діяльності та її вплив на формування професійно-соціальних компетентностей.налізуючи досвід використання волонтерської діяльності на факультеті фізичного виховання та спорту ХДУ зазначимо, що вона сприяє формуванню професійного досвіду, розвитку етичної свідомості; стимулює розвиток мотиваційної сфери студента, його особистісних якостей, спрямованості до саморозвитку, розширення професійної компетентності
Волонтерство у форму-ванні компетентностей майбутніх фахівців із фізичної культури та спорту.
Keywords: competence; volunteer activity; vocational training; students; functions; directions; компетентності; волонтерська діяльність; професійна підготовка; студенти; функції; напрями